Peran GBKP Pamulang dalam Mengatasi Krisis Ekologi - Nofyn, Hafizzatul; Nurdin, M. Amin (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2024)
This research analyzes the role of the Batak Karo Protestant Church (GBKP) in Pamulang in addressing the ecological crisis. The main focus of this study is how GBKP implements the service theme